Ideas and society in India from the sixteenth to the eighteenth centuries - Vanina, Eugenia (Delhi, 1996)
This work discusses society and ideas in India between the 16th and 18th centuries as seen by medieval and early modern thinkers. It also deals with the reaction of Indian thought to the culture and presence of the West in India, and the author attempts to study medieval Indian history in a global perspective. The book is intended for students and researchers interested in medieval India, and those interested in studying history in a comparative global perspective may also find it of value.
Keywords: Societies-India-16th to 18th centuries